Determinants of Household Biogas-Bioslurry Economic Benefits: Linear Mixed Model with Cost-Benefit and Sensitivity Analysis - Wijaya, Shirley; Iskandar, Mario; Daud Unas, Hardiono Arron (Riviera Publishing, 2025)
The increasing demand for sustainable energy solutions in rural areas has prompted the utilization of biogas and bio-slurry as alternative resources. This study aims to evaluate the economic feasibility of household-level biogas systems by integrating Cost-Benefit Analysis (CBA), Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Undiscounted Payback Period (UPBP), complemented with sensitivity analysis. Primary data were collected from 16 households operating biogas systems, while secondary data supported the estimation of cost and benefit components. Results show that biogas adoption provides positive economic returns, with average NPV reaching Rp 12,749,000, BCR above 1.0, and UPBP within four years, indicating financial viability. Sensitivity analysis reveals that variations in LPG prices and livestock numbers significantly affect economic outcomes, demonstrating the importance of market and production factors in ensuring project sustainability. The findings conclude that household biogas systems are economically feasible and resilient under certain conditions. Future studies are suggested to expand the scope by incorporating environmental and social benefits, as well as exploring scalability at the community level.